The Problem Management of Picky Eating in Preschool Children Based on Complementary and Alternative Therapy - Widia Shofa Ilmiah; Rifzul Maulina; Anik Sri Purwanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Picky eating is a prevalent issue among preschool children, often leading to nutritional deficiencies, disrupted growth, and increased parental stress. This systematic literature review aims to explore the management of picky eating through complementary and alternative therapies (CAT) and compares these findings with contemporary interventions. Picky eating behaviors can significantly affect children’s eating patterns, leading to challenges in maintaining a balanced diet. Although traditional medical interventions focus on behavioral modification and nutritional counseling, many parents are seeking alternative approaches to manage these behaviors in a more holistic and natural manner. This review encompasses studies published between 2015 and 2025, sourced from PubMed, Scopus, and Google Scholar, using keywords such as